Propionate production from carbon monoxide by synthetic cocultures of acetobacterium wieringae and propionigenic bacteria - Moreira, João Paulo Carvalho (2021)
Gas fermentation is a promising way to convert CO-rich gases to chemicals. We studied the use of synthetic cocultures composed of carboxydotrophic and propionigenic bacteria to convert CO to propionate. So far, isolated carboxydotrophs cannot directly ferment CO to propionate, and therefore, this cocultivation approach was investigated. Four distinct synthetic cocultures were constructed, consisting of Acetobacterium wieringae (DSM 1911T) and Pelobacter propionicus (DSM 2379T), Ac. wieringae (DSM 1911T) and Anaerotignum neopropionicum (DSM 3847T), Ac. wieringae strain JM and P. propionicus (DSM 2379T), and Ac. wieringae strain JM and An. neopropionicum (DSM 3847T). Propionate was produced by all the cocultures, with the highest titer (;24mM) being measured in the coculture composed of Ac. wieringae strain JM and An. neopropionicum, which also produced isovalerate (;4mM), butyrate (;1mM), and isobutyrate (0.3mM). This coculture was further studied using proteogenomics. As expected, enzymes involved in the Wood-Ljungdahl pathway in Ac. wieringae strain JM, which are responsible for the conversion of CO to ethanol and acetate, were detected; the proteome of An. neopropionicum confirmed the conversion of ethanol to propionate via the acrylate pathway. In addition, proteins related to amino acid metabolism and stress response were highly abundant during cocultivation, which raises the hypothesis that amino acids are exchanged by the two microorganisms, accompanied by isovalerate and isobutyrate production. This highlights the importance of explicitly looking at fortuitous microbial interactions during cocultivation to fully understand coculture behavior.